RIS-Assisted Hexagonal Receive QSM Technique with Perfect and Imperfect Channel Estimation - Cogen, Fatih; Ozden, Burak Ahmet; Aydin, Erdogan (IEEE, 2024)
Nowadays, there is a need for high-performance and energy-efficient communication systems due to the rapid increase in the number of mobile users and the demand for better quality communication due to the development of technology. Reconfigurable intelligent surface (RIS) technology, which reduces the interference effects of the wireless fading channel, and receive quadrature spatial modulation (RQSM) technique, which significantly increases the data rate and system performance compared to conventional communication systems, are important systems that aim to meet the above-mentioned demands and needs. In addition, the application of energy-efficient hexagonal quadrature amplitude modulation (HQAM) techniques on next-generation communication techniques has recently become a popular topic. HQAM optimizes the assignment of codewords to points in a hexagonal constellation diagram to minimize the average Hamming distance, reducing error rates by keeping similar codewords close together. This arrangement is always more energy efficient than conventional QAM modulation and provides similar performances as QAM. In this paper, a scheme called RIS-HQAM-RQSM is proposed by combining the techniques of rational RIS, RQSM, and HQAM. The performance analysis of the proposed system is carried out for different numbers of reflecting surfaces and receiving antennas over Rayleigh fading channels using HQAM modulation. Furthermore, the performance of the proposed system is compared with significant peer systems in the literature, and it is observed that the proposed system achieves better error performance than benchmark systems with the same spectral efficiency. Also, performance analyses of the system in both perfect channel knowledge (PCK) and imperfect channel knowledge (ICK) are obtained.
Keywords: Reconfigurable intelligent surface; QAM; hexagonal QAM; spatial modulation; quadrature spatial modulation; MODULATION; Computer Science; Engineering; Telecommunications